2017
DOI: 10.2147/dddt.s140164
|View full text |Cite
|
Sign up to set email alerts
|

Isatin-benzoazine molecular hybrids as potential antiproliferative agents: synthesis and in vitro pharmacological profiling

Abstract: In continuation of our endeavor with respect to the development of potent and effective isatin-based anticancer agents, we adopted the molecular hybridization approach to design and synthesize four different sets of isatin-quinazoline (6a–f and 7a–e)/phthalazine (8a–f)/quinoxaline (9a–f) hybrids. The antiproliferative activity of the target hybrids was assessed towards HT-29 (colon), ZR-75 (breast) and A-549 (lung) human cancer cell lines. Hybrids 8b–d emerged as the most active antiproliferative congener in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Isatin (1H-indole-2, 3-dione), a precursor for many pharmacologically active compounds, [2][3][4] is an important medicinal chemistry. 5 Isatin derivatives have extensive biological activities, such as antitumor, anti-HIV, antiinflammatory, anti-convulsion, antidepressant, and antifungal effects, 5 attracting much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Isatin (1H-indole-2, 3-dione), a precursor for many pharmacologically active compounds, [2][3][4] is an important medicinal chemistry. 5 Isatin derivatives have extensive biological activities, such as antitumor, anti-HIV, antiinflammatory, anti-convulsion, antidepressant, and antifungal effects, 5 attracting much attention.…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer SAR of hybrids 56 against HT‐29, ZR‐75, and A549 cancer cell lines revealed that substituent at the C‐5 position of isatin skeleton influenced the activity greatly and halogen atom could improve the activity. [ 117 ] Three of them, 56a–c (IC 50 : 5.31–13.25 μM, MTT assay), were comparable to or better than sunitinib (IC 50 : 5.87–10.14 μM) against HT‐29, ZR‐75, and A549 cancer cell lines, and compound 56b (IC 50 : 9.5 μM) was also active against multidrug‐resistant NCI‐H69AR lung cancer cells. Moreover, this hybrid exhibited an increase in the G1 phase and a decrease in the S and G2/M phases in the cell‐cycle effect assay.…”
Section: Isatin–coumarin Hybridsmentioning
confidence: 99%
“…It is thought that conjugating two or more pharmacophoric subunits from different biologically active molecules in the molecular architecture of a single hybrid compound might reduce the risk of drug-drug interactions, overcome the drug resistance, and enhance the biological activity via the potential interaction with two targets as one single entity [31]. In this field, our research group has reported many studies concerning the development of efficient oxindole-based anticancer hybrids (hybrids I-III [32][33][34], Figure 1) that exhibited different enzymatic and cellular targets such as apoptosis induction in different human cancer cell lines [35,36], inhibition of cancer-related carbonic anhydrase IX isoform [37,38], in addition to inhibition of tyrosine kinases [39,40].…”
Section: Introductionmentioning
confidence: 99%